The impact of previous authorization to the administrative contract conclusion- Comparative Study (Damascus University Journal for legal sciences, 2021)
The legislator imposes on administration at the stage of administrative contract formation a number of restrictions and controls which administration should commit to.These restrictions appear in the need of having financial provision for the process to be concluded, this financial provision can be at the general State budget or at the budget of the public moral persons at the decentralized level.In fact, having the financial provision is not enough for administration to conclude the contract, it is also bounded to have a contractual authorize from the competent authority. Weather this authority was the legislative authority, executive power or the judicial authority. It is the same weather the prospective contractor was an administrative body at the state level or a decentralized level.As this legal rules of financial provision and contractual authorize are made by the legislator, then the administration responsibility arises in the case of breaking these rules.The comparative doctrine and judiciary decided at the case of administration responsibility not to affect the contract in specific cases, but in other cases decided the administrative responsibility and the contract illegality together.The contract illegality means that no contractual relation is existed, which causes that no contractual responsibility rules can be applied. Here the French State Council came to find a legal solution about that by establishing a semi contractual relation between the two parties, and according to this relation the compensation is given to the second part, especially if the declaration of illegality comes after implementation of contract commitments. and so did the state council in both Egypt and Syria with differences in some cases.
Keywords: The impact of previous authorization to the administrative contract conclusion- Comparative Study